First approach to unilateral transfemoral amputees' contact mechanics (2017)
The stresses in the hip area have great importance because of their relationship to the health of the joint. Finite element models can predict contact between cartilages, however, contact patterns in unilateral transfemoral amputees have not yet been found in literature. We thus want to present an initial approach in the contact mechanics of the hip joint of these amputees. From an existing database, three transfemoral amputees who use prostheses were chosen. Their respective hips and femur were obtained from tomography, and so as their cartilages from their respective articular surfaces. Finite element models were created per patient and static bipedestation was analyzed. At the beginning of contact between cartilages, contact stresses were determined. The results showed that the stresses of the amputated side were higher than that of the non-amputated, in terms of average and peak contact stress. These were located in the anterior and superior zones, respectively.